Cerebrovascular accident and myocardial infarction associated with anticardiolipin antibodies in a young woman with systemic lupus erythematosus. Issue 10 (October 1989) - Maaravi, Y; Raz, E; Gilon, D; Rubinow, A
Abstract : A 26 year old woman with systemic lupus erythematosus, including malar rash, photosensitivity, and arthritis, developed a cerebrovascular accident and acute myocardial infarction. High titres to antinuclear factor, anti-DNA antibodies, positive Venereal Disease Research Laboratory (VDRL) test, and anticardiolipin antibodies were found in her serum. A possible association between the presence of anticardiolipin antibodies and the two major thrombotic events is discussed.